2019
DOI: 10.1111/scd.12360
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sensory adapted dental environment on children with developmental disabilities

Abstract: Aims This was a pilot study assessing the impact of a sensory adapted dental environment (SADE) on children with developmental disabilities (DD) receiving routine dental care. Methods A crossover study of 22 children with DD, aged 6 through 21, was conducted at a University Pediatric Dental clinic. Each participant was randomized to a sequence of two dental cleanings on a 3‐ to 4‐month recall schedule, one with a regular dental environment (RDE) and one with SADE. Outcomes included physiological measures (hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(90 citation statements)
references
References 23 publications
3
84
1
2
Order By: Relevance
“…They revealed that children with IDD showed higher levels of relaxation and cooperation in the SADE compared with routine dental environment (RDE). Similarly, two other recent studies observed the efficacy of SADE on dental anxiety of children with IDD ( n = 22) [50] and adults with IDD ( n = 41) [51]. Potter et al [51] added to the evidence with both reduced frequency and duration of agitated behaviours in the SADE condition, whereas Shapiro et al [52] only recorded the duration.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…They revealed that children with IDD showed higher levels of relaxation and cooperation in the SADE compared with routine dental environment (RDE). Similarly, two other recent studies observed the efficacy of SADE on dental anxiety of children with IDD ( n = 22) [50] and adults with IDD ( n = 41) [51]. Potter et al [51] added to the evidence with both reduced frequency and duration of agitated behaviours in the SADE condition, whereas Shapiro et al [52] only recorded the duration.…”
Section: Resultsmentioning
confidence: 94%
“…GIC helps to reduce plaque accumulation, although retention of the GIC on tooth surfaces was inadequate. 1d). Dental clinic setting Kim, Carrico, Ivey & Wunsch, 2019 (USA) [50]Crossover RCTExplore impact of a sensory adapted dental environment (SADE) on behavioural and physiological changes when compared to routine dental environment (RDE).Children with developmental disability (male n = 14, female n = 8)No significant difference in physiological scores (heart rate and oxygen saturation) between the two groups. The SADE group had significantly better observed behaviour scores compared to the routine dental environment group. Potter, Wetzel & Learman, 2018 (USA) [51]Cohort studyExamine whether a SADE had an effect on anxiety and agitation in adults with IDD when compared to RDE.Adults with IDD (male n = 22; female n = 19) mainly with severe to profound IDD.There was a significant reduction in the frequency and duration of observed agitation after SADE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, these may involve facilitating communication, reducing anxiety associated with unfamiliar providers and routines, and sensory-based approaches to reduce triggers and use helpful soothing strategies. [77][78][79] A more detailed discussion of these strategies can be found in a 2019 review in Psychosomatics by Thom and colleagues. 73 Pharmacologic interventions for pediatric inpatients with ASD include management of comorbid psychiatric symptoms, such as anxiety or hyperactivity, identifying medications, such as corticosteroids, that have the potential to exacerbate behavioral difficulties, and preventing and treating disruptive behaviors.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%